Knowth before Knowth - Eogan, George
Recent research at the great Irish passage tomb of Knowth has revealed new decorated stones, which were apparently recycled from an earlier tomb. Here, George Eogan describes the finds and discusses the implication of an early phase of tomb building pre-dating the major passage tombs of the Boyne Valley..